Long‐term decline in abundance of male sperm whales visiting Kaikōura, New Zealand. Issue 2 (1st November 2021) - Somerford, Tamlyn R.; Dawson, Stephen M.; Slooten, Elisabeth; Guerra, Marta; Childerhouse, Simon J.; Richter, Christoph F.; van der Linde, Miranda L.; Rayment, William J.
Abstract: Kaikōura, New Zealand, is one of the few places worldwide where sperm whales can be routinely found close to the coast. Although whales are present nearly all year round, no individuals are truly resident. In this study, we analyzed photo‐identification data collected over 27 years to investigate long‐term trends in inshore abundance. We contrasted two analytical approaches: Cormack‐Jolly‐Seber (CJS) mark‐recapture models, and the "Robust Design, " which can incorporate temporary emigration of individuals. CJS models for open populations showed a significant decline in the annual number of individual males, from 89, 95% CI [60, 133] in 1991, to 40, 95% CI [33–49] in 2017. The Robust Design models indicated that the trend was driven by a decline in abundance of whales using Kaikōura during summer, from 54, 95% CI [18, 156] in 1990, to 23, 95% CI [16, 33] in 2017. In contrast, there was no evidence for change in the numbers of whales using Kaikōura during winter. Incorporating temporary emigration had the most support, indicating Robust Design was more appropriate for estimating abundance. The results of Pradel recruitment models suggest that recruitment to the population using the study area during summer declined during the late 1990s/early 2000s, potentially explaining the decline in abundance.